Social enterprise and impact investment beyond the benefit corporation : trust, public benefit and capital markets - Reiser, Dana Brakman; Dean, Steven A. (Oxford University Press, 2017)
By providing a comprehensive survey of the U.S. laws and a bold vision for how legal institutions across the globe could be reformed, Social Enterprise Law offers new insights and approaches to help social enterprises raise the capital they need to flourish. It offers a rich guide for students, entrepreneurs, investors, and practitioners. -- Resumé vydavatele